Recruitment for Voluntary Video and Mobile HIV Testing on Social Media Platforms During the COVID-19 Pandemic: Cross-Sectional Study - Piao-Yi Chiou; Wei-Wen Tsao; Chia-Lin Li; Jheng-Min Yu; Wen-Han Su; Zhi-Hua Liu; Cheng-Ru He; Yu-Chun Chang; Yi-Hsuan Tsai (JMIR Publications, 2024)
BackgroundThe COVID-19 pandemic prompted social distancing policies and caused misinformation that hindered in-person HIV screening for high-risk groups. Social media platforms provide additional options for voluntary counseling and testing (VCT) for HIV, overcoming these limitations. However, there is a lack of data on HIV testing recruitment through social media platforms and its outcomes during the pandemic. ObjectiveThis study aimed to measure the rate of face-to-face mobile and video VCT conducted after recruitment through social media platforms and friend referrals during the pandemic and compare the geographic distribution, risk feature targeting, testing outcome, and cost between the 2 models. MethodsData were collected from March 3 to December 31, 2021, during the COVID-19 outbreak in Taiwan. Participants engaging in unprotected sex were recruited. After one-on-one message discussions through the platforms, the well-trained research assistants provided mobile or video VCT based on the participants' availability. Primary outcomes were completion rate, testing results, and CD4 count. Secondary outcomes included demographic and HIV risk-taking and protective features from a questionnaire. Selection bias was controlled by adjusting for the testing site (Taipei vs non-Taipei) using univariable multinomial logistic regression. ResultsThis study gathered 5142 responses on the social media platforms, recruiting 1187 participants. Video VCT had a completion rate of 31.8% (207/651), higher than mobile VCT's 21.8% (980/4491). Both rates were higher than those before the COVID-19 pandemic. Recruitment through friend referrals, instant messaging apps (eg, Line [LY Corporation]), and geosocial dating apps (eg, Hornet [Queer Networks Inc], Grindr [Grindr LLC], and Gsland [Tien-Hao Tsai]) resulted in higher acceptance and completion rates than social networks (eg, Facebook [Meta], X [formerly Twitter], and Instagram [Meta]). Mobile VCT had higher recruitment among urban residents and screening density, while video VCT reached a broader geographic area. The mobile group was more likely to have had more than 10 sexual partners (odds ratio [OR] 1.92, 95% CI 1.05-3.50; P=.03), history of sex work (OR 4.19, 95% CI 1.68-10.43; P=.002), and sexually transmitted diseases (OR 2.23, 95% CI 1.18-4.23; P=.01) within the past 3 months. The video group was more likely to meet sexual partners through social media. The HIV-positive rate in the mobile group was 0.7% (7/973) with an average CD4 count of 460/μL, while in the video group, it was 1% (2/205) with an average CD4 count of 347/μL, indicating a later diagnosis. Both positivity rates were higher than those before the COVID-19 pandemic, with no significant difference between the groups. The video group cost US $54.68 per participant, slightly higher than the US $50.36 for the mobile group. ConclusionsRecruiting through social media platforms that facilitate one-on-one message discussions can effectively target high-risk groups for mobile and video VCT. This approach should be integrated into the current screening model to enhance HIV case finding.